2008
DOI: 10.1097/ta.0b013e31815eb142
|View full text |Cite
|
Sign up to set email alerts
|

Automatically-Computed Prehospital Severity Scores are Equivalent to Scores Based on Medic Documentation

Abstract: Methods:In a retrospective analysis of trauma casualties transported by air ambulance, we computed the Triage Revised Trauma Score (RTS) from archived travel monitor data. We compared the areas-under-the-curve (AUC's) of receiver operating characteristic curves for prediction of mortality and red blood cell transfusion for 187 subjects with comparable quantities of good-quality and poorquality data.Results: Vital signs deemed reliable by SQI's led to significantly more discriminatory severity scores than vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…21 • The blood pressure reliability algorithm compares the HR measured by an oscillometric noninvasive blood pressure cuff versus the ECG HR and also checks that the relationships between SBP, MAP, and DBP are physiologic. 22 Reliable SBP, as determined by this algorithm, was found to be statistically superior to unreliable SBP as a predictor of major hemorrhage.…”
mentioning
confidence: 99%
“…21 • The blood pressure reliability algorithm compares the HR measured by an oscillometric noninvasive blood pressure cuff versus the ECG HR and also checks that the relationships between SBP, MAP, and DBP are physiologic. 22 Reliable SBP, as determined by this algorithm, was found to be statistically superior to unreliable SBP as a predictor of major hemorrhage.…”
mentioning
confidence: 99%
“…Vital sign data rated 2 or 3 were considered reliable; otherwise, they were unreliable. Detailed descriptions of these algorithms have been previously reported [28][29][30]. Here, we provide an overview of the methodology.…”
Section: Vital Sign Reliabilitymentioning
confidence: 98%
“…The BP reliability algorithm determined if the ratio between SBP, DBP, and mean pressure is physiologic and if the HR measured by the inflatable oscillometric cuff matches the ECG HR [29]. The algorithm does not attempt to distinguish between unequal HRs because of motion artifact vs unequal HRs because of nonperfusing electrical beats, for example, premature contractions; in the latter case, it would be possible for reliable BP data to be misclassified as unreliable.…”
Section: Vital Sign Reliabilitymentioning
confidence: 99%
“…We previously found that automated techniques are diagnostically equivalent to prehospital severity scores based on medics' documentation. 15 In this case, we focused on the identification of hemorrhage because blood loss is 1 of the 2 primary reasons why trauma patients die, 35,36 but in many cases it can be treated effectively with blood transfusion and surgical hemorrhage control. We speculate that formal quantitative analysis of continual vital signs may be able to supplement today's convention, which relies on informal clinician judgments to integrate vital-sign data with other important clinical data.…”
Section: Discussionmentioning
confidence: 99%